Hot-streak effect on internally air-cooled nozzle guide vanes and shrouds. (7th October 2019) - Jiang, L. Y.; Han, Y.; Zhang, Z.; Wu, X.; Clement, M.; Patnaik, P.
ABSTRACT: The effect of hot streaks from a gas turbine combustor on the thermodynamic load of internally air-cooled nozzle guide vanes (NGVs) and shrouds has been numerically investigated under flight conditions. The study follows two steps: one for the high-fidelity 60° combustor sector with simplified ten NGVs and three thermocouples attached; and the other for the NGV sectors where each sector consists of one high-fidelity NGV (probe NGV) and nine dummy NGVs. The first step identifies which NGV has the highest thermal load and provides the inlet flow boundary conditions for the second step. In the second step, the flow fields and thermal loads of the probe NGVs are resolved in detail. With the systematically validated physical models, the two-phase flowfield of the combustor-NGVs sector has been successfully simulated. The predicted mean and maximum temperature at the combustor sector exit are in excellent agreement with the experimental data, which provides a solid basis for the hot-streak effect investigation. The results indicate that the second NGV, looking upstream from left, has the highest thermal load. Its maximum surface temperature is 8.4% higher than that for the same NGV but with the mean inlet boundary conditions, and 14.1% higher than the ninth NGV. The finding is consistent with the field-observed NGV damage pattern. To extend the service life of these vulnerable NGVs, some protection methods should be considered.